Beneath the Tip of the Pandemic Iceberg - Agarwal, Gina; Dzerounian, Jasmine (My University, 2021)
What's hidden beneath the tip of the pandemic iceberg? As Ontario and other regions across Canada reopen, we look forward to working with paramedic services to safely restart CP@clinic and CP@home programming.
Keywords: Community Paramedicine; Primary Care; Vulnerable Populations; Social Housing; Paramedics; Validated Health Risk Assessment